ANALISIS SISTEM PENGAWASAN TERHADAP PRODUK YANG TERSERTIFIKASI HALAL DI BAKSO MAMA 1 JOMBANG - Auliyaur Rokhman (Istithmar: Jurnal Studi Ekonomi Syariah, 2021)
This research is motivated by the number of employees who during service activities / present products do not wear production equipment such as gloves, aprons, so that the product becomes unhygienic and can result in the quality of the product becomes decreased. In addition, there are some employees who serve customers while smoking. Of course, this is very uncomfortable with this situation, because cigarette smoke is not good for health and harms others. Departing from the background, obtained 3 problem formulations namely: 1) how production supervision applied in Bakso Mama 1 Jombang? 2) how is the standard halal product in Bakso Mama 1 Jombang? 3) what is the role of production supervision in Bakso Mama 1 Jombang? The research method used is Qualitative by using Triangulation. The results showed that: 1) Implementation of production control system applied by meatballs mama 1 jombang can already be said in accordance with the 6 indicators of production supervision that is characterized by the absence of errors / delays in work that has been targeted by meatballs mama 1 jombang. And there is no forced or pressure felt by employees during the work with the supervision system imposed. 2) Implementation of product quality standards applied to meatballs mama 1 Jombang is in accordance with the 6 indicators of service quality and has met all indicators that must be present in halal products that have been mentioned in UU No. 33 tahun 2014 on Halal Product Guarantee. 3) The role of supervision in improving the quality of products in Bakso Mama 1 Jombang is a. to supervise and assist the task of a leader in realizing the vision and mission of the company, b. to establish good relations between employees and leaders through the completion of all production work in a timely manner, c. maintaining the halalness of products, d. maintaining public health, e. protecting the right of consumers to obtain halal products.